Proliferative and Apoptotic Pathways in the Testis of Quail Coturnix coturnix during the Seasonal Reproductive Cycle - Sara Falvo; Luigi Rosati; Maria Maddalena Di Fiore; Federica Di Giacomo Russo; Gabriella Chieffi Baccari; Alessandra Santillo (Animals, 2021)
The quail Coturnix coturnix is a seasonal breeding species, with the annual reproductive cycle of its testes comprising an activation phase and a regression phase. Our previous results have proven that the testicular levels of both 17β-estradiol (E2) and androgens are higher during the reproductive period compared to the non-reproductive period, which led us to hypothesize that estrogens and androgens may act synergistically to initiate spermatogenesis. The present study was, therefore, aimed to investigate the estrogen responsive system in quail testis in relation to the reproduction seasonality, with a focus on the molecular pathways elicited in both active and regressive quail testes. Western blotting and immunohistochemistry analysis revealed that the expression of ERα, which is the predominant form of estrogen receptors in quail testis, was correlated with E2 concentration, suggesting that increased levels of E2-induced ERα could play a key role in the resumption of spermatogenesis during the reproductive period, when both PCNA and SYCP3, the mitotic and meiotic markers, respectively, were also increased. In the reproductive period we also found the activation of the ERK1/2 and Akt-1 kinase pathways and an increase in second messengers cAMP and cGMP levels. In the non-reproductive phase, when the E2/ERα levels were low, the inactivation of ERK1/2 and Akt-1 pathways favored apoptotic events due to an increase in the levels of Bax and cytochrome C, with a consequent regression of the gonad.